2007
DOI: 10.1074/jbc.m610818200
|View full text |Cite
|
Sign up to set email alerts
|

Munc18c Interaction with Syntaxin 4 Monomers and SNARE Complex Intermediates in GLUT4 Vesicle Trafficking

Abstract: In the process of insulin-stimulated GLUT4 vesicle exocytosis, Munc18c has been proposed to control SNARE complex formation by inactivating syntaxin 4 in a self-associated conformation. Using in vivo fluorescence resonance energy transfer in 3T3L1 adipocytes, co-immunoprecipitation, and in vitro binding assays, we provide data to indicate that Munc18c also associates with nearly equal affinity to a mutant of syntaxin 4 in a constitutively open (unfolded) state (L173A/E174A; LE). To bind to the open conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…Indeed, wild type (WT) EGFP-tagged syntaxin 4 showed a similar lateral localization as untagged syntaxin 4. We and others have previously shown the importance of the first 8 amino acids of the N-terminal sequence for munc18c binding (7,36,37). However, transient expression of syntaxin 4 with N-terminal deletions up to 15 amino acids had no major effects on the localization of syntaxin 4 ( Fig.…”
Section: N-terminal Region Of Syntaxin 4 Contains Basolateral Sortingmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, wild type (WT) EGFP-tagged syntaxin 4 showed a similar lateral localization as untagged syntaxin 4. We and others have previously shown the importance of the first 8 amino acids of the N-terminal sequence for munc18c binding (7,36,37). However, transient expression of syntaxin 4 with N-terminal deletions up to 15 amino acids had no major effects on the localization of syntaxin 4 ( Fig.…”
Section: N-terminal Region Of Syntaxin 4 Contains Basolateral Sortingmentioning
confidence: 73%
“…Indeed, residual interaction between syntaxin 4 mutated in the N-peptide has been reported, as Latham and co-workers (10) found some interaction between syntaxin 4-L8K pulled down with munc18c-GST munc18c. Using FRET analysis it has been shown that another syntaxin 4 N-peptide mutant deficient in munc18c binding interacts in vivo with munc18c (37). Also, we have previously shown that syntaxin 4 without the N-terminal peptide binds munc18c (7) in vitro.…”
Section: Discussionmentioning
confidence: 92%
“…Once on the cell surface, GLUT4 facilitates the uptake of excess blood glucose into the cells for disposal (20,21). Although insulin secretion and GLUT4 exocytosis are regulated by distinct trigger signals, both pathways require syntaxin-4 and SNAP-23 as the t-SNAREs, and VAMP2/synaptobrevin as the primary v-SNARE (22)(23)(24)(25)(26). In insulin secretion, the vesicle fusion reaction also involves another t-SNARE complex, syntaxin-1 and SNAP-25 (25)(26)(27).…”
mentioning
confidence: 99%
“…However, it has been dis-puted that this N-terminal region of syntaxin 4 can independently confer binding specificity to the Munc18c isoform, as opposed to binding Munc18a or Munc18b (Munc18a and Munc18b specifically bind syntaxin isoforms 1-3). Thus, it has been suggested there are likely alternate or additional residues required to support and specify the association (37,38).…”
mentioning
confidence: 99%